A PK Experiment with Zebra Finches and a Virtual Predator - Gonzalez, Fernando Alvarez (Journal of Scientific Exploration, 2012)
The hypothesis that PK is a biological function which can be used by prey animals to their own benefit was tested using 25 zebra finches. To test whether birds can manipulate the randomness of REG devices in a virtual predatory context, experimental and control trials were run. During the former, one subject was placed in the testing cage and could see a 25-frames-per-second, 150-second-duration video clip of a crawling predatory snake in a TFT-LCD screen. Immediately before each image, a REG device would randomly increase or decrease by one point the opacity of the subsequent image, which, as a consequence, would become more solid or more transparent. During the control test no subject was present in the testing cage. When the REG outcome was analyzed, the total number of events of image fading was found to be significantly higher for the experimental condition than for the control condition, and during the experimental condition the number of image fadings was also significantly higher than that of opacity increases (and non-significant during the control condition). Therefore, the birds might be able to influence the REG production to reduce the presence of the predator (i.e. the proposed hypothesis appears to be supported). Keywords: birds—PK—predation—zebra finches